2020
DOI: 10.1101/2020.07.26.20154724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interim Results of a Phase II/III Multicenter Randomized Clinical Trial of AVIFAVIR in Hospitalized Patients with COVID-19

Abstract: In May 2020 the Russian Ministry of Health granted fast-track marketing authorization to RNA polymerase inhibitor AVIFAVIR (favipiravir) for the treatment of COVID-19 patients. In the pilot stage of Phase II/III clinical trial, AVIFAVIR enabled SARS-CoV-2 viral clearance in 62.5% of patients within 4 days, and was safe and well-tolerated.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 5 publications
0
54
1
1
Order By: Relevance
“…LPV/r 2.Umifenovir Exploratory Randomized Controlled Trial 400/100 mg twice daily for 4-weeks LPV/r or Umifenovir alone shows little benefit in COVID-19 patients Li et al, 2020 124 ChiCTR2000029600 80 Hospitalized patients with moderate-severe COVID-19 Favipiravir An Open-Label Control Single-Centre Trial FPV 1600 mg twice daily, then 600 mg twice daily for day 2–14 Favipiravir produced faster recovery in COVID-19 patients than the control group Cai et al, 2020 123 jRCTs041190120. 69 Hospitalized patients with moderate COVID-19 Favipiravir A Prospective, Randomized, Open-Label, Multicenter Trial 1800 mg twice 4 h apart day 1, then 800 mg twice for 10 days Favipiravir did not significantly improve COVID-19 viral clearance within 6 days Doi et al, 2020 129 NCT04434248 60 Hospitalized patients with moderate COVID-19 Favipiravir A Prospective, Open Label, Randomized Multicenter -Clinical Trial 1600mg twice day 1, then 600mg twice day 2–14 Favipiravir significantly improve COVID-19 viral clearance within 5 days Ivashchenko et al, 2020 130 ChiCTR2000030254 240 Hospitalized patients with severe COVID-19 1. Favipiravir 2.Umifenovir Prospective Randomized, Open-Label, Multicenter Controlled Trial 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPV/r 2.Umifenovir Exploratory Randomized Controlled Trial 400/100 mg twice daily for 4-weeks LPV/r or Umifenovir alone shows little benefit in COVID-19 patients Li et al, 2020 124 ChiCTR2000029600 80 Hospitalized patients with moderate-severe COVID-19 Favipiravir An Open-Label Control Single-Centre Trial FPV 1600 mg twice daily, then 600 mg twice daily for day 2–14 Favipiravir produced faster recovery in COVID-19 patients than the control group Cai et al, 2020 123 jRCTs041190120. 69 Hospitalized patients with moderate COVID-19 Favipiravir A Prospective, Randomized, Open-Label, Multicenter Trial 1800 mg twice 4 h apart day 1, then 800 mg twice for 10 days Favipiravir did not significantly improve COVID-19 viral clearance within 6 days Doi et al, 2020 129 NCT04434248 60 Hospitalized patients with moderate COVID-19 Favipiravir A Prospective, Open Label, Randomized Multicenter -Clinical Trial 1600mg twice day 1, then 600mg twice day 2–14 Favipiravir significantly improve COVID-19 viral clearance within 5 days Ivashchenko et al, 2020 130 ChiCTR2000030254 240 Hospitalized patients with severe COVID-19 1. Favipiravir 2.Umifenovir Prospective Randomized, Open-Label, Multicenter Controlled Trial 1.…”
Section: Resultsmentioning
confidence: 99%
“… 129 However, two recent clinical trials revealed that FPV administered to COVID-19 patients showed a faster recovery than the control group. 130 , 131 Overall, there is currently insufficient evidence to suggest that the FPV has significant antiviral activity against COVID-19 and could be recommended as a future treatment.…”
Section: Resultsmentioning
confidence: 99%
“…There are conflicting articles regarding both HCQ and favipiravir [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. However, studies conducted in different countries, with patients from differing ethnicities, with different endpoints/outcomes, and different designs should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, 3 arms (1800 mg BID x 2 doses then 800 mg BID (high dose) vs. 1600 mg BID x 2 doses then 600 mg BID (low dose) vs. placebo) were studied in hospitalized COVID-19 patients in Russia. Favipiravir was associated with more rapid clearance of PCR and resolution of fever [3] . In the second open-label study, 89 Japanese patients were randomized to early vs late therapy for asymptomatic or mild COVID-19 using high dose favipirivir.…”
mentioning
confidence: 91%